2016
DOI: 10.1177/1524838015596528
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Instrumentality and Expressiveness of Homicide Crime Scene Behaviors

Abstract: Homicide offender typologies developed based on crime scene behaviors have practical utility for scholarly and criminal investigative endeavors. Hence, there has been an increasing interest to develop empirical and testable offender typologies. Specifically, the present study offers a review of the instrumental/expressive offender dichotomy, which is developed primarily based on the analysis of (nonsexual) homicide crime scene behaviors. The validity of the instrumental/expressive dichotomy of homicide offende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
3
25
0
1
Order By: Relevance
“…However, the serial cases did to a higher extent display instrumental crime scene behaviour such as stranger and female victim, planning, strangulation, forensic awareness, and staging. Even though no statistical testing was conducted regarding the instrumental/expressive dichotomy, this study lends support to the evidence reported by Adjorlolo and Chan ().…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the serial cases did to a higher extent display instrumental crime scene behaviour such as stranger and female victim, planning, strangulation, forensic awareness, and staging. Even though no statistical testing was conducted regarding the instrumental/expressive dichotomy, this study lends support to the evidence reported by Adjorlolo and Chan ().…”
Section: Discussionsupporting
confidence: 87%
“…Another interesting circumstance is the difference between single‐ and serial‐homicide offences in relation to the instrumental/expressive dichotomy of crime scene behaviour. Adjorlolo and Chan () has in their review on the instrumental/expressive dichotomy concluded that there is strong evidence for the typology from different homicide samples but also different settings. As found in Table , it is evident that the single‐homicide offences in this study to a higher extent involved expressive crime scene behaviour such as intoxication, blunt violence and knife, acquainted victims, defence wounds, and that the victim was hit several times.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual violence is generally construed as instrumental, that is, as a means to gain something or some advantage with a measure of forethought or expressive so committed in anger or as a response to perceived provocation (see Adjorlolo & Chan, ). Burgess, Hartman, Ressler, Douglas, and McCormack () defined sexual homicide as the “result from one person killing another in the context of power, control, sexuality, and aggressive brutality” (p. 252).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, many research studies have established a homicide classification, based on the Instrumental/Expressive dichotomy of aggressive behavior (Salfati and Park, 2007;Goodwill et al, 2014;Adjorlolo and Chan, 2015;Sea and Beauregard, 2017;Pecino-Latorre et al, 2019b). However, some authors consider that the Instrumental/Expressive instrument is an excessive simplification of the violence as it attributes the behavior to only one psychological construct (Häkkänen et al, 2004b;Thijssen and De Ruiter, 2011).…”
Section: Introductionmentioning
confidence: 99%